2018
DOI: 10.1039/c8cp00551f
|View full text |Cite
|
Sign up to set email alerts
|

Band bending and dipole effect at interface of metal-nanoparticles and TiO2 directly observed by angular-resolved hard X-ray photoemission spectroscopy

Abstract: This paper describes the observation of band bending and band edge shifts at the interfaces between nanoscale metals and TiO2 film over a wide depth range by angular-resolved hard X-ray photoemission spectroscopy (HAXPES). The HAXPES results indicate strong electrostatic interactions between the TiO2 semiconductor and metal nanoparticles, while density functional theory (DFT) calculations suggest that these interactions are primarily associated with charge transfer leading to electric dipole moments at the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 50 publications
(59 reference statements)
1
17
0
Order By: Relevance
“…Since 2013 a considerable number of studies performed at the beamline using an X-ray energy of 7.94 keV have provided insights into predominantly structured, multilayer samples for device applications. [68,[239][240][241] AR-HAXPES was identified as a useful technique to study such multilayer systems from the beginning, including the first HAXPES paper at SPring-8 which explored the θ dependence of the Si 1s spectra of a HfO 2 /SiO 2 /Si system. [29] Of particular interest in such studies are changes to the band positions at interfaces, including band bending and rigid band edge shifts, which can be inferred from core level shifts as a function of distance from a surface or interface.…”
Section: Angular-dependent Haxpes (Ar-haxpes)mentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2013 a considerable number of studies performed at the beamline using an X-ray energy of 7.94 keV have provided insights into predominantly structured, multilayer samples for device applications. [68,[239][240][241] AR-HAXPES was identified as a useful technique to study such multilayer systems from the beginning, including the first HAXPES paper at SPring-8 which explored the θ dependence of the Si 1s spectra of a HfO 2 /SiO 2 /Si system. [29] Of particular interest in such studies are changes to the band positions at interfaces, including band bending and rigid band edge shifts, which can be inferred from core level shifts as a function of distance from a surface or interface.…”
Section: Angular-dependent Haxpes (Ar-haxpes)mentioning
confidence: 99%
“…explored the interaction of nanoscale metal particles, including Pt, Au and Rh, with TiO . [239] In combination with density functional theory calculations they were able to identify electrostatic interactions taking place, which influenced not only the surface and interfaces, but the bulk properties of TiO 2 . This study showcases the crucial information AR-HAXPES can provide on device-relevant structures.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In the case of conventional TiO 2 electrodes, it was reported that loading of nanoscale metals Rh, Pt, and Au on TiO 2 electrode surfaces changes their electronic states such as surface charges and band‐bending characteristics . Rh showed the largest negative shift of Ti 2p, indicating an upward band bending toward the TiO 2 surface as a result of a surface‐charge equilibrium that induces a surface dipole moment.…”
Section: Further Challenges For Stabilizing the Photoreaction And Undmentioning
confidence: 99%
“…Rh showed the largest negative shift of Ti 2p, indicating an upward band bending toward the TiO 2 surface as a result of a surface‐charge equilibrium that induces a surface dipole moment. DFT calculations explained this tendency nicely, attributing it to the ionization energy values for these metals . The lower ionization energy for metals generally increases the charge transfer in the vicinity of the oxygen in TiO 2 .…”
Section: Further Challenges For Stabilizing the Photoreaction And Undmentioning
confidence: 99%
See 1 more Smart Citation